Advertisement Tax Contribution To Regional Original Income In Pinrang Regency - Muthmainnah Milliani (Pustaka Digital Indonesia, 2021)
This study aims to determine how big the contribution of advertising tax to Regional Original Income in Pinrang Regency for the 2016-2020 period. The type of research used is a quantitative research method with the presentation of data predominantly in the form of numbers and statistical data analysis. The data processed is time series data from 2011-2020 obtained from the Regional Revenue Service Office of Pinrang Regency. The data collection technique used in this research is library research in the form of books, articles and others related to research. While the data analysis technique used is to use the contribution formula where the advertisement tax is divided by the Regional Original Revenue and then multiplied by 100%. Based on the results of the analysis and collection of advertisement tax data on Regional Original Revenue in 2011-2020 it can be concluded that the advertisement tax contribution in 2011 was 0.27%, in 2012 it was 0.32 %, in 2013 it was 0.23 %, in 2014 it was 0.23%. 0.16 %, in 2015 it was 0.17 % in 2016 it was 0.17%, in 2017 it was 0.19%, in 2018 it was 0.18%, in 2019 it was 0.18%, and in 2020 it was 0.21%.